Rapid inactivation and sample preparation for SARS-CoV-2 PCR-based diagnostics using TNA-Cifer Reagent E - Pollak, Nina M.; Rawle, Daniel J.; Yan, Kexin; Buckley, Cameron; Le, Thuy T.; Wang, Claire Y. T.; Ertl, Nicole G.; van Huyssteen, Karla; Crkvencic, Nicole; Hashmi, Misha; Lyons, Russell E.; Whiley, David M.; et al. (Frontiers in Microbiology, 2023)
RT-qPCR remains a key diagnostic methodology for COVID-19/SARS-CoV-2. Typically nasal or saliva swabs from patients are placed in virus transport media (VTM), and RNA is extracted at the pathology laboratory and viral RNA measured using RT-qPCR. Herein we describe the use of TNA-Cifer Reagent E in a pre-clinical evaluation study to both inactivate SARS-CoV-2 and prepare samples for RT-qPCR. Addition of 1 part TNA-Cifer Reagent E to 5 parts medium containing SARS-CoV-2 for 10 min at room temperature inactivated virus and permitted RT-qPCR detection. TNA-Cifer Reagent E was compared with established column-based RNA extraction and purification methodology using a panel of human clinical nasal swab samples (n=61), with TNA-Cifer Reagent E showing high specificity (100%) and sensitivity (97.37%). Mixtures of SARS-CoV-2 virus and TNA-Cifer Reagent E could be stored for 3 days at room temperature or for 2 weeks at 4°C without loss of RT-qPCR detection sensitivity. Detection sensitivity was preserved when TNA-Cifer Reagent E was used in conjunction with a range of VTMs for saliva samples, but only PBS (Gibco) and Amies (Orange) for nasal samples. TNA-Cifer Reagent E thus improves safety by rapidly inactivating the virus during sample processing, potentially providing a safe means for molecular SARS-CoV-2 testing outside traditional laboratory settings. The reagent also removes the requirement for column-based and/or automated viral RNA extraction/purification processes, thereby providing cost savings for equipment and reagents, as well as reducing processing and handling times.